A Shocking Complication of a Pneumothorax: Chest Tube-Induced Arrhythmias and Review of the Literature - Shaun Cardozo; Kevin Belgrave (Case Reports in Cardiology)
We describe a patient with a recent chest tube insertion leading to atrial fibrillation with rapid ventricular rate that led to multiple inappropriate internal cardiac defibrillator (ICD) shocks. This is the first reported case of this occurring in a patient with an ICD leading to inappropriate shocks. Our elderly patient with emphysema presented with a spontaneous pneumothorax and developed rapid atrial fibrillation following emergency tube thoracostomy. The patient had a single lead ICD and received multiple inappropriate shocks for the rapid ventricular rate in the therapy zone. Although medical treatment helped stabilize the patient, resolution of the atrial fibrillation occurred only after the chest tube was removed. In a patient with a chest tube or other intrathoracic catheters, maintaining a high index of suspicion that chest tube insertions can cause secondary life threatening cardiovascular complications needs to be considered. In such patients, removal of the device proves to be the most prudent treatment action.